The sea wolves eaudiobook - Du Brul, Jack (Isaac Bell, 2022)
Detective Isaac Bell battles foreign spies, German U-boats, and an old nemesis to capture a secret technology that could alter the outcome of World War I in the latest adventure in the #1 New York Times bestselling series from Clive Cussler. As New England swelters in the summer of 1914, Detective Isaac Bell is asked to investigate the disappearance of a cache of rifles—only to discover something much more sinister. Whoever broke into this Winchester Factory wasn’t looking to take weapons, they wanted to leave something in the shipping crates: a radio transmitter, set to summon a fleet of dreaded German U-boats. Someone is trying to keep American supplies from reaching British shores, and if Bell doesn’t crack the conspiracy in time, the Atlantic Ocean will run red with blood. Bell must hunt down a new piece of technology that is allowing the Germans to rule the seas from New York to England. With the outcome of the war at stake and Franklin Roosevelt’s orders on the line, Bell will risk everything to stop the U-Boats before they strike again.